Metronomic delivery of orally available pemetrexed-incorporated colloidal dispersions for boosting tumor-specific immunity. (1st January 2021) - Maharjan, Ruby; Subedi, Laxman; Pangeni, Rudra; Jha, Saurav Kumar; Kang, Seo Hee; Chang, Kwan-Young; Byun, Youngro; Choi, Jeong Uk; Park, Jin Woo
Abstract: In this study, we developed oral pemetrexed (PMX) for metronomic dosing to enhance antitumor immunity. PMX was electrostatically complexed with positively charged lysine-linked deoxycholic acid (DL) as an intestinal permeation enhancer, forming PMX/DL, to enhance its intestinal permeability. PMX/DL was also incorporated into a colloidal dispersion (CD) comprised of the block copolymer of poly(ethylene oxide) and poly(propylene oxide), and caprylocaproyl macrogol-8 glycerides (PMX/DL-CD). CD-containing PMX/DL complex in a 1:1 molar ratio [PMX/DL(1:1)-CD] showed 4.66- and 7.19-fold greater permeability than free PMX through the Caco-2 cell monolayer and rat intestine, respectively. This resulted in a 282% improvement in oral bioavailability in rats. In addition, low-dose metronomic PMX led to more immunogenic cell death in CT26.CL25 cells compared to high PMX concentrations at the maximum tolerated dose. In CT26.CL25 tumor-bearing mice, oral metronomic PMX/DL-CD elicited greater antitumor immunity not only by enhancing the number of tumor-infiltrating lymphocytes but also by suppressing T cell functions. Oral PMX/DL-CD substantially increased programmed cell death protein ligand-1 (PD-L1) expression on tumor cells compared to the control and PMX-IV groups. This increased antitumor efficacy in combination with anti-programmed cell death protein-1 (aPD-1) antibody in terms of tumor rejection and immunological memory compared to the combination of PMX-IV and aPD-1. These results suggest that oral metronomic scheduling of PMX/DL-CD in combination with immunotherapy has synergistic antitumor effects.